Effect of electrode heating on the distribution of the ion production rate in a capacitively coupled plasma deposition reactor in consideration of thermal decomposition. (July 2021) - Kim, Ho Jun
Abstract: In the semiconductor industry, the electrode in a capacitively coupled plasma (CCP) deposition reactor is often heated to modulate the properties of the material or to adjust the film deposition rate. Because the gas density is governed by the ideal gas law, electrode heating induces local depletion of the source density near the corresponding sheath. Thus, spatial variations in the plasma parameters such as the ion production rate, electron density, and radical density can be efficiently controlled by changing the electrode temperature. SiH4 /He CCP was studied as an example of the deposition of a hydrogenated amorphous silicon film by varying the mole fraction of SiH4 and gas pressure. The effect of the thermal decomposition of SiH4 was investigated by increasing the electrode temperature up to 1273 K. Contrary to expectation, the peak electron densities increased at higher electrode temperatures, for a higher source fraction, and at higher gas pressure. The critical findings that emerged from the simulation results were validated by comparing them with the experimental observations. Although the heater temperature was varied, the simulated deposition rate profiles and deposition rates were in good correspondence with the experimental data in terms of both the average value and the profile shape. Highlights: Effects of electrode heating on plasma distribution in a CCP reactor were studied. The model included thermal decompositions such as SiH4 ↔ SiH2  + H2 in the reaction. Input conditions such as the mole fraction of SiH4 and the pressure were varied. Deposition rate profiles were non-uniform although plasma distribution was uniform. Reactions of heavy molecules become significant at the considered higher pressures.